The Relationship between School Welfare and Learning Motivation for Upper Grade Elementary School Students: Hubungan Antara School Well-Being dengan Motivasi Belajar pada Siswa Kelas Tinggi Sekolah Dasar - Soifidah, Anvi Ridatus; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the phenomenon of high grade elementary school students who lack the motivation to learn where these students when facing assignments or homework given by the teacher are not done, rely on homework from smart friends, complain when they get homework, and imitate the work of friends. . This study aims to determine the relationship between school well-being and learning motivation in high grade students at SDN Lambangan. This research includes correlational quantitative research. The population in this study were 83 students consisting of class IV, class V, and class VI. The sampling technique used in this research is saturated sampling. Data collection techniques in this study used 2 scales, namely, the school well-being scale consisting of 42 items and the learning motivation scale consisting of 27 items. The hypothesis in this study is that there is a positive relationship between school well-being and learning motivation in high-class students at SDN Lambangan. The results of this study indicate that the correlation coefficient is 0.420 with a significance value of p = 0.000 <0.05. The result of the determination coefficient test is 0.165 which indicates that the school well-being variable in this study has an influence of 16.5% on the learning motivation variable. These results indicate that the hypothesis proposed in this study is accepted.